2002
DOI: 10.1046/j.1365-8711.2002.05024.x
|View full text |Cite
|
Sign up to set email alerts
|

A radio study of neutral gas and dust in the radio galaxy 3C 293

Abstract: We have observed broad H i absorption in the radio galaxy 3C 293 using Multi‐Element Radio Linked Interferometric Network (MERLIN) at 0.2‐arcsec angular resolution and the Giant Meterwavelength Radio Telescope (GMRT) at arcsec resolution. Extensive H i is found in absorption across the centre of this peculiar radio galaxy, allowing a detailed study of the dynamics of the neutral gas on linear scales down to ∼160 pc. In optical depth position–velocity diagrams across the central few kpc we detect a distinct vel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
75
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(91 citation statements)
references
References 23 publications
13
75
3
Order By: Relevance
“…In this galaxy, very broad H I absorption has been detected against the central regions -this is in addition to the known and much narrower absorption; Haschick & Baan 1985, Beswick et al 2002 Left: a zoom-in of the [0111] and Ha+ [NII] lines in the Seyfert IC 5063. The radio image on a similar scale is also shown.…”
Section: Outflows Of Neutral Hydrogenmentioning
confidence: 83%
“…In this galaxy, very broad H I absorption has been detected against the central regions -this is in addition to the known and much narrower absorption; Haschick & Baan 1985, Beswick et al 2002 Left: a zoom-in of the [0111] and Ha+ [NII] lines in the Seyfert IC 5063. The radio image on a similar scale is also shown.…”
Section: Outflows Of Neutral Hydrogenmentioning
confidence: 83%
“…Since our observations, four sources have been studied with other telescopes. NGC 315 is presented in Morganti et al (2009); 3C 293 was observed at high resolution by Beswick et al (2002); and NGC 5141 and NGC 7052 were observed at lower resolution in Emonts et al (2010). Only NGC 7052 was not detected, and a stringent upper-limit was set.…”
Section: Vla Observationsmentioning
confidence: 97%
“…These images (except Fig. 3(d), which is reproduced directly from Beswick, Pedlar & Holloway (2002)), are obtained reducing the archival VLA data in a standard manner using the AIPS package. Figure 2 shows the 1.36 GHz VLA B-array (project code GP022) image of the outer lobes (this map is similar to that shown by Beswick et al 2004 in their Fig.…”
Section: Radio Maps and Datamentioning
confidence: 99%
“…In particular, Lanz et al extracted the spectrum of the nuclear region in the circular 3. 5 aperture (radius of ∼ 3 kpc) centred at the radio core precisely determined with the MERLIN/VLA/VLBI observations (Beswick, Pedlar & Holloway 2002;Beswick et al 2004) and discovered that it could be fitted with a model consisting of a thermal component with a temperature of 1.03 ± 0.10 keV, and two power-law components: one absorbed (N H = 9.4 × 10 22 cm −2 ) with the photon index of 1.32 ± 0.36, and the other one unabsorbed with the photon index of 0.57 ± 0.87. The authors associated the absorbed power-law component with the active nucleus, while the unabsorbed power law and the thermal components with an off-nuclear source and a diffuse emission around the nuclear region, respectively.…”
Section: Hot Gaseous Environmentmentioning
confidence: 99%
See 1 more Smart Citation